Disparity in the Use of Mass Media among Youth Population in Nepal - Thapa, Shyam (Nepal Public Policy Review, 2023)
This paper assesses disparities in the use of mass media among the youth population in Nepal. Data for this cross-sectional analysis were extracted from the Nepal Demographic and Health Survey undertaken in 2016. The total sample of 8,010 included four population sub-groups – single and married males, and single and married females, ages 15-24. The forms of mass media assessed included reading the newspaper, watching TV, listening to the radio, or using the internet. Binary logistic multiple regression was applied to assess the net effects of covariates on the use of specific forms of mass media. Of the four types of mass media, TV was the most commonly used (52%), and newspaper and internet were the least used (14%). Radio was used by 34%. Any of the four types of mass media was used by 72%, while only 1% of youth used all four types. Household wealth status, followed by the educational background of the youth and their region of residence, were the main factors significantly and strongly correlated with the disparity in mass media use. Compared to single or married males or single females, married females were the least likely to use any of the forms of mass media. The results show that despite rapid growth in mass media over the last 25 years in Nepal, great disparities still persist in the current use of mass media among the youth population, particularly based on gender and marital status. The findings underscore the need for media-based interventions to be sensitive to both the gaps related to gender and marital status among the youth population in Nepal.